PROMOTING NON-VIOLENT PARENTING AMONG REFUGEE MOTHERS IN DURBAN - Umubyeyi, Beatrice; Harris, Geoff (Social Work/Maatskaplike Werk, 2014)
This research began by examining the attitudes and behaviour of mothers from the Durban refugee community regarding the use of corporal punishment in bringing up children. Its use was found to be widespread and frequent among a sample of 50 mothers. A training course in non-violent parenting was designed and administered to 16 mothers. A very preliminary evaluation suggests that there were significant shifts of attitude among the participants in favour of non-violent parenting.